Role of The Perludem and Its Implications Through The Judicial Review Article 414 of The General Election Law - Bobby; Mustofa, Mustabsyirotul Ummah (Candidate: Jurnal Sains Politik, 2025)
This paper seeks to explain Perludem's role in strengthening democracy in Indonesia and how the non-governmental organization influences government through in-depth research into the constitutional court's judicial review of Article 414 of the Election Law on the parliamentary threshold. The analysis using qualitative methods based on a literature review highlights Perludem's successful advocacy strategy in advocating for inclusive policies and illustrates the important role of civil society in safeguarding the sustainability of democracy. Perludem argued that high parliamentary thresholds undermine the principle of democratic representation, leaving millions of valid votes unrepresented in parliament. Although the verdict showed that the article was constitutional for the 2024 elections and the Constitutional Court did not change the numerical threshold, the decision needs to be revisited by lawmakers by applying the principle of fairness to the 2029 elections.